2019
DOI: 10.1177/2382120519888915
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Scoping Review of Ethical Issues in Mentoring in Surgery

Abstract: Background: Mentoring is crucial to the growth and development of mentors, mentees, and host organisations. Yet, the process of mentoring in surgery is poorly understood and increasingly mired in ethical concerns that compromise the quality of mentorship and prevent mentors, mentees, and host organisations from maximising its full potential. A systematic scoping review was undertaken to map the ethical issues in surgical mentoring to enhance understanding, assessment, and guidance on ethical conduct. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 163 publications
(508 reference statements)
0
20
0
Order By: Relevance
“…Two recent reviews into the potential sources of ethical issues in mentoring in medicine and surgery found that mentoring assessment tools continue to intermix of mentoring with coaching, supervision, tutoring and role-modelling and conflate distinct mentoring practices such as novice, near-peer, peer, group, mosaic, network and e-mentoring and mistakenly [20,[37][38][39][40][41]. In addition Lee et al (2019) [42] and Cheong et al (2019) [43] found that prevailing assessments of mentoring processes are too reliant upon "Cartesian reductionism and Newtonian principles of linearity" [28] and fail to contend with mentoring's longitudinal, competency based, evolving, adapting, entwined, goal-sensitive, context-specific, mentor-, mentee-, mentoring relationship and host organisation-dependent nature (henceforth mentoring's nature) [44,45]. These shortcomings compromise effective evaluations of mentoring processes and relationships and reiterate the need for urgent review of assessments of mentoring processes [42,43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent reviews into the potential sources of ethical issues in mentoring in medicine and surgery found that mentoring assessment tools continue to intermix of mentoring with coaching, supervision, tutoring and role-modelling and conflate distinct mentoring practices such as novice, near-peer, peer, group, mosaic, network and e-mentoring and mistakenly [20,[37][38][39][40][41]. In addition Lee et al (2019) [42] and Cheong et al (2019) [43] found that prevailing assessments of mentoring processes are too reliant upon "Cartesian reductionism and Newtonian principles of linearity" [28] and fail to contend with mentoring's longitudinal, competency based, evolving, adapting, entwined, goal-sensitive, context-specific, mentor-, mentee-, mentoring relationship and host organisation-dependent nature (henceforth mentoring's nature) [44,45]. These shortcomings compromise effective evaluations of mentoring processes and relationships and reiterate the need for urgent review of assessments of mentoring processes [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…In addition Lee et al (2019) [42] and Cheong et al (2019) [43] found that prevailing assessments of mentoring processes are too reliant upon "Cartesian reductionism and Newtonian principles of linearity" [28] and fail to contend with mentoring's longitudinal, competency based, evolving, adapting, entwined, goal-sensitive, context-specific, mentor-, mentee-, mentoring relationship and host organisation-dependent nature (henceforth mentoring's nature) [44,45]. These shortcomings compromise effective evaluations of mentoring processes and relationships and reiterate the need for urgent review of assessments of mentoring processes [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, mentoring has come under increased scrutiny amidst suggestions that mentoring relationships are poorly assessed and supported [2][3][4]. These gaps are seen to aggravate power dynamics between mentee and mentor [2] and predispose to grave issues such as bullying and even sexual harrassment [3,4]. These reports have curtailed mentoring's role in medical school education, hampering the provision of personalised, longitudinal and holistic support [5][6][7], career guidance [8][9][10][11][12][13][14][15], and research opportunities [16][17][18][19][20][21][22] to medical students.…”
Section: Introductionmentioning
confidence: 99%
“…With mentoring playing a key role in training medical students and with many ethical issues poorly described [2,23], a systematic scoping review (SSR) is proposed to map prevailing descriptions of ethical issues in mentoring in medical schools to guide a structured and evidence-based response [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation